Parenting with nutrition education and unconditional cash reduce maternal depressive symptoms and improve quality of life: findings from a cluster randomised controlled trial in urban Bangladesh - Sheikh Jamal Hossain; Fahmida Tofail; Anisur Rahman; Jane Fisher; Jena Derakhshani Hamadani; Syed Moshfiqur Rahman (Global Health Action)
Background Maternal post-natal depression is a global public health problem. Parenting interventions targeting children’s development may also bring benefits to mothers, but few parenting interventions have been studied thoroughly. Objectives The study aimed to measure the effect of a parenting intervention using culturally appropriate and locally made toys, along with nutrition education and unconditional cash, on maternal depressive symptoms (MDS) and quality of life (QoL). Methods The study was a cluster randomised controlled trial with two arms: i) intervention: parenting with nutrition education and unconditional cash and ii) comparison: unconditional cash in an urban setting in Bangladesh. Twenty clusters were randomised to either the intervention or control group. Community Health Workers (CHWs) delivered parenting and nutrition education sessions fortnightly in households for one year. The participants were mother-child (6–16 months) dyads. The MDS and QoL were measured using the Self-Reporting Questionnaire-20 and a brief version of the QoL questionnaire. Linear regression analysis was used to assess the treatment effects. Results After one year of intervention, 547 mothers (93%) completed the study. The mothers in the intervention group had lower MDS [Regression coefficient (β)=-1.53, Confidence interval (95% CI)=-2.28, −0.80] and higher QoL scores in physical health [β = 4.21 (95% CI = 1.71, 6.73)], psychological health [β = 3.14 (95% CI = 1.10, 5.19)], social relationships [β = 3.21 (95% CI = 0.76, 5.66)] and environment [β = 3.40 (95% CI = 1.37, 5.44)] compared with the comparison group. Conclusion Parenting interventions including nutrition education and unconditional cash, aimed at improving children’s development, resulted in a reduction in maternal depressive symptoms and improvement in quality of life.